2020
DOI: 10.1111/cns.13285
|View full text |Cite
|
Sign up to set email alerts
|

Pain relief and improvement in quality of life with 10 kHz SCS therapy: Summary of clinical evidence

Abstract: Objective Chronic pain is a prevalent condition which has a significant effect on the lives of those it impacts. High‐frequency 10 kHz spinal cord stimulation (10 kHz SCS) has been shown to provide paresthesia‐free pain relief for a wide variety of pain indications. This article summarizes the current and emerging data as they relate to the clinical use of the therapy in various pain syndromes. Methods A literature search was conducted using the PubMed electronic database using keywords related to 10 kHz SCS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 72 publications
(149 reference statements)
5
38
0
Order By: Relevance
“…Pain intensity showed rapid and continued improvement throughout the study period, and the responder rate compares favorably to previous studies of 10‐kHz SCS in other pain conditions, including the SENZA‐RCT randomized controlled trial, which reported response rates of 84.5% for back pain and 83.1% for leg pain, and other real‐world and prospective studies 15–17,28–35 . The remission rate was 62.1% (18 subjects) after 1 year of treatment, which is very similar to the rate from SENZA‐RCT, which was about 60%.…”
Section: Discussionsupporting
confidence: 78%
“…Pain intensity showed rapid and continued improvement throughout the study period, and the responder rate compares favorably to previous studies of 10‐kHz SCS in other pain conditions, including the SENZA‐RCT randomized controlled trial, which reported response rates of 84.5% for back pain and 83.1% for leg pain, and other real‐world and prospective studies 15–17,28–35 . The remission rate was 62.1% (18 subjects) after 1 year of treatment, which is very similar to the rate from SENZA‐RCT, which was about 60%.…”
Section: Discussionsupporting
confidence: 78%
“…The SENZA-RCT and other published studies of 10 kHz-SCS have demonstrated that a substantial proportion of patients experience sustained pain relief considerably greater than 50%, with sustained pain scores of ≤3.0 (on a 0 to 10 VAS)—so-called “remitter” state. 9 , 10 , 20 , 33 , 35 , 37 42 This contrasts with the assumption in the model that treatment had been successful if patients achieved ≥50%: the real-world outcomes with use of 10 kHz-SCS are better than this. 38 Research into the HRQoL and health care costs of remitters would enable an update of the existing SCS economic model.…”
Section: Discussionmentioning
confidence: 78%
“…The evidence for the efficacy of 10‐kHz SCS relieving chronic pain in multiple contexts, improving patients’ quality of life, and reducing opioid consumption, 20,21 and its efficacy in treating CPP is supported by a small case series 13 . Unlike SCS at lower frequencies, animal models suggest 10‐kHz SCS selectively activates inhibitory interneurons in the spinal dorsal horn at low intensities below the threshold activating the dorsal column 22 .…”
Section: Discussionmentioning
confidence: 99%